2008
DOI: 10.1111/j.1742-4658.2008.06470.x
|View full text |Cite
|
Sign up to set email alerts
|

The metalloprotease PrtV from Vibrio cholerae

Abstract: Vibrio cholerae, the causative agent of cholera, is a Gram-negative motile bacterial species acquired via ingestion of contaminated food or water. Little is known regarding the environmental survival factors that exist in V. cholerae and play an important role in maximizing the ability of the vibrios to survive and multiply in the environment interacting with predators. In a recent study, we established that Caenorhabditis elegans is useful as a model system for identifying and assessing factors from V. choler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 44 publications
2
54
0
Order By: Relevance
“…This protein cleaves host antibacterial proteins. Homologs of the immune inhibitor A, named PrtV, have been found in V. cholerae and V. anguillarum (Vaitkevicius et al, 2006(Vaitkevicius et al, , 2008. PrtV is required for killing C. elegans and has a cytotoxic effect, leading to cell death.…”
Section: Vibrio Coralliilyticus Genome E De O Santos Et Almentioning
confidence: 99%
“…This protein cleaves host antibacterial proteins. Homologs of the immune inhibitor A, named PrtV, have been found in V. cholerae and V. anguillarum (Vaitkevicius et al, 2006(Vaitkevicius et al, , 2008. PrtV is required for killing C. elegans and has a cytotoxic effect, leading to cell death.…”
Section: Vibrio Coralliilyticus Genome E De O Santos Et Almentioning
confidence: 99%
“…Bacterial extracellular proteases often undergo multiple proteolytic cleavage steps that lead to the conversion of a pre-proenzyme (an inactive precursor) into a mature protein (44). In V. cholerae, both well-characterized metalloproteases, HapA and PrtV, are subjected to a maturation process that includes several N-and C-terminal modification steps during translocation across the cell envelope and prolonged incubation (45)(46)(47).…”
Section: Fig 4 Extracellular Localization Of Vchc Is Affected By the mentioning
confidence: 99%
“…For example, the extracellular metalloprotease PrtV of Vibrio cholerae is required for host-killing [46], and the zinc metalloprotease EmpA of Vibrio anguillarum is a virulence factor that participates in pathogen-host interactions [47][48][49][50]. Both PrtV and EmpA are known to be cytotoxic to cultured host cells [51,52]. In our study, we found that, like EmpA and PrtV, Vhp1 exhibited apparent cytotoxicity to cultured flounder cells, which suggests the possibility that Vhp1 may play a role in the pathogenesis of V. harveyi by destructing the cellular barrier of host defense.…”
Section: Discussionmentioning
confidence: 99%